The Determination and Analysis of Deformations in a Soil Under Dynamic Loading - Krzywicki, Henry (My University, 1964)
This Thesis describes a method for determining and analysing the deformations in peat caused by a driven rigid wheel. Markers were placed in the peat sample and radiographs were taken as the wheel travelled over the surface of the peat. An analysis of the data revealed that a unique relationship existed between the positions of the markers and the positions of the wheel. The paths of the principal stress trajectories were determined by a graphical method; from the principal stress trajectories, it was possible to find the surfaces of maximum shear. The purpose of determining these surfaces is to allow the equilibrium of the soil mass to be investigated by the present theories in soil mechanics; it is to draw an analogy to the analysis of slope stability problems.
Keywords: deformation; soil; dynamic loading; deformation analysis; soil mechanics; slope stability